Best Foot Forward or Best for Last in a Sequential Auction? - Archishman Chakraborty; Nandini Gupta; Rick Harbaugh (Claremont McKenna College, Department of Economics, 2000)
Should an informed seller of multiple goods sell the best goods first to make a favorable impression on buyers, or instead hold back on the best goods until buyers have learned more from earlier sales? To help answer this question we consider the sequential auction of two goods by a seller with private information about their values. We find that the seller's sequencing strategy endogenously generates correlation in the values of the goods across periods, thereby giving the seller an incentive to impress buyers by leading with the better good. This impression effect implies that selling the better good first is the unique equilibrium in many situations, and that selling the better good last is never a unique equilibrium. Nevertheless, if the seller could commit to a sequencing strategy, revenues would often be higher from waiting to sell the better good last. Either sequencing strategy reveals the seller's ranking of the goods and thereby, due to the linkage principle, generates higher revenues than either randomly selling the goods or selling them simultaneously.
Keywords: D44; D82; 330; sequential auction; impression effect; linkage principle; declining price anomaly